Perlindungan Hukum Terhadap Hubungan Induk Perusahaan Dan Anak Perusahaan Dalam Holding Company BUMN - Sativa Nisya Padmawati; Aisyah Adilla (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The economic world in Indonesia has grown rapidly as the times, the numbers of jobs that have expanded along with the increase in demand for jobs in Indonesia and inceasing bussines competition. Over time, holding companies have become an option for companies in Indonesia. Holding Company becomes the main company that organize the parent company and oversees the management of several subsidiaries that are members of one grup of companies. This company is a type of limited liability company that aims to organize, manage and oversee the perfomance of company. Bankcrupty is a risk that can occur in a company both to the parent company and subsidiaries in a BUMN holding company.